ACUPUNCTURE AND ITS HEALTH BENEFITS - Burack, Dionizia; Ferreira Dos Santos Reitez, Zeloí; Bertassoni Alves, Hermerson (Health and Society, 2022)
The objective of this work is to present the benefits in acupuncture for the quality of life of people, studying the elements and resources of acupuncture, being applied needles in specific points to treat diseases. It also analyzes the causes of anxiety and shows the results through the therapy and the study of its indications and contraindications. The research was conducted through literature review and health articles that address the diseases and pathophysiology, diagnosis and treatment of diseases. The results of the patients who use this therapy bring a better quality of life, returning energy to the body, feeling lighter and more comfortable. It is a low cost therapy and immediate result in which diseases without administration of medications or even with them are treated.